Peranan Penyuluh Pertanian Terhadap Perilaku Perempuan Tani Dalam Kegiatan Usahatani Jagung Di Desa Tempos, Kecamatan Gerung, Kabupaten Lombok Barat - Fajriani, Nurdani; Hayati, Hayati; Muktasam, Muktasam (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This study aims to determine the role of agricultural extension workers on the behavior of women farmers in corn farming activities in Tempos Village, Gerung Subdistrict, West Lombok Regency. This research was conducted using survey methods and interviews with 60 female farmer respondents. The results showed that the role of agricultural extension officers did not affect the behavior of women farmers in maize farming activities. The female farmer respondents knew the importance of various aspects of maize farming, such as seed preparation, land preparation, ploting and planting, fertilization, irrigation, pest and disease control, and harvesting. However, they did not show significant differences in maize farming behavior between those who received guidance from agricultural extension agents and those who did not. The results of this study can be used for consideration in the development of a more effective maize farming mentorship program